P1-S2.14 Neisseria gonorrhoea and Chlamydia trachomatis Re-infection and associated risk factors among cohort of female sex workers in India. (10th July 2011) - Risbud, A R; Deshpande, G R; Narayanan, P; Parimi, P; Das, Anjana
Abstract : Background: Neisseria gonorrhoea (NG) and Chlamydia trachomatis (CT) infections can be completely cured by appropriate medication. Syndromic STI management often fails to cover asymomatic NG/CT infections. Additionally, Female sex workers (FSWs), due to their risky behaviour are vulnerable to repeated infections. Frequency of repeated infections with these pathogens was studied in a cohort of FSWs. Methods: In 6 months prospective cohort study, FSWs aged 18–40 years were recruited from three STI clinics in two states in India as a part of Bill & Melinda Gates Foundation funded operational research. Vaginal swab specimens were collected in all visits and were tested for NG/CT by Gen-Probe APTIMA Combo II assay. Presumptive treatment for gonorrhoea and chlamydia at the baseline visit and syndromic STI management at all subsequent visits was provided during the study period. Re-infection was defined as a laboratory confirmed NG/CT infection occurring after 30 days from an initial confirmed positive test result. Results: Of 417 FSWs recruited during 2008–2009, 360 made at least 1-monthly follow-up visit. At baseline and during follow-up, 184 were NG infected and 210 were CT infected see Abstract P1-S2.14 Table 1 . A total of 39 (11.8%) NG re-infections and 30 (8.3%) CT re-infections were identified at follow-up visits. Among the factors studied, alcohol consumption (OR=2.4, p=0.01); relatively new to commercial sex work (within 3 years) (OR=2.16, p=0.03); had STIs in the past (OR=3.85, p=0.00) were significantly associated with the NG, CT re-infection. Conclusion: High frequency of NG and CT re-infection among FSWs highlights the need for regular screening for etiological diagnosis for effective treatment. New sex workers and those consuming alcohol need special attention in STI management.